Where do perceptions lie? Assessing corruption perceptions in Brazil - Senra, Pedro Henrique Vieira (2022)
Corruption perceptions barely changed in Brazil between 2014 and 2021. In this period, protests against public spending and corruption spurred political turmoil, culminating in a presidential impeachment. Numerous anticorruption measures were enacted amidst an investigation that scourged higher echelons of political elites, including two former presidents. These factors expectedly impacted corruption perceptions, the dominating measure of corruption, especially the Corruption Perceptions Index (CPI). Perceptions must draw from something; yet the CPI has been found unrelated to objective data, corruption victimization, or experiences. To this end, this piece assessed the interplay between the CPI, corruption’s salience on Brazil’s media, and a novel measure of anticorruption capacity formed by the number of corruption indictments, proceedings, and the Ministry of Justice’s budget, which represents investigative resources. Only the latter bears a highly significant – and negative – relationship with the CPI; its interviewees interpret additional investigative resources under a worse corruption outlook. It seems perceptions do lie, just not where expected. These results bring the CPI further into question; scholars and practitioners should be wary of adopting it.